2021
DOI: 10.1051/e3sconf/202126102045
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted pyrolysis of seaweed biomass for aromatics-containing bio-oil production

Abstract: Microwave-assisted pyrolysis of seaweed biomass was conducted using a microwave pyrolysis system. The product yields were determined and the components of bio-oil were analyzed by a gas chromatography-mass spectrometry (GC-MS). Results showed that as the pyrolysis temperature increased from 400 °C to 600 °C, the gas yield increased and the bio-char yield decreased. However, the bio-oil yield rose firstly and then reduced. The maximal bio-oil yield was 18.4 wt.% when pyrolysis temperature was 500 °C. The bio-oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The agricultural industry, which accounts for 12% of all global GHG emissions, is one of the top three CO 2 emitters [5,6]. Studies have shown that both the energy business and the agricultural sector offer prospects for lowering GHG emissions [7].…”
mentioning
confidence: 99%
“…The agricultural industry, which accounts for 12% of all global GHG emissions, is one of the top three CO 2 emitters [5,6]. Studies have shown that both the energy business and the agricultural sector offer prospects for lowering GHG emissions [7].…”
mentioning
confidence: 99%